Block Level Analysis of Rainfall and Temperature Trends and Variability Across Districts of Chhattisgarh, India - , Dhanapriya M, Gowtham S (Archives of Current Research International, 2025)
Various rainfall and temperature patterns in 149 blocks of Chhattisgarh in India were analyzed for trends and variability from January 01, 2023 to March 31, 2024. Using Innovative Trend Analysis (ITA), the study considered four major climatic variables for five times: annual, winter, summer, southwest monsoon, and northeast monsoon. The variables under study are rainfall, the number of rainy days, maximum temperature, and minimum temperature. The study also concludes that climatic changes differ very much depending on location and the season. According to the studies, maximum temperatures have been increasing steadily across the state, while there has been a general decrease in annual rainfall and the number of rainy days. The findings provide insight into climatic variability in Chhattisgarh, which may influence agricultural practices and future planning concerning climate resilience.